2004
DOI: 10.1097/01.jom.0000131830.45744.97
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Health Risks and Work Productivity

Abstract: We sought to provide evidence for the relationship between health risks and self-reported productivity, including health-related absence and impaired performance on the job. A cross-sectional analysis was implemented consisting of 2264 employees of a large national employer located in the Northeast. Participants responded to a health risk assessment and work productivity scale. Mean productivity loss was compared for individuals with different levels of risk factors using analysis of variance. Multivariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
238
1
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(290 citation statements)
references
References 18 publications
23
238
1
12
Order By: Relevance
“…Workers with depression report a loss of nearly 6 hours of productive time per week, whereas in the control group, lost productive time was 75% lower (Stewart, Ricci et al, 2003a; similar results are reported by Adler, Irish et al, 2004;and Marciniak, Lage et al, 2004). A study of special significance with respect to regional considerations was that conducted by Boles, Pelletier et al (2004), where it was shown that employees with higher health risks report higher levels of impaired performance on the job.…”
Section: Comparison With Earlier Research!supporting
confidence: 62%
“…Workers with depression report a loss of nearly 6 hours of productive time per week, whereas in the control group, lost productive time was 75% lower (Stewart, Ricci et al, 2003a; similar results are reported by Adler, Irish et al, 2004;and Marciniak, Lage et al, 2004). A study of special significance with respect to regional considerations was that conducted by Boles, Pelletier et al (2004), where it was shown that employees with higher health risks report higher levels of impaired performance on the job.…”
Section: Comparison With Earlier Research!supporting
confidence: 62%
“…The study showed health risks as follows were most prevalent: high cholesterol, 47%; physical inactivity, 45%; high stress, 29%; and lack of emotional fulfillment, 24%. Employees with physical inactivity were significantly more likely to be both absent and impaired on the job compared with employees who did participate in physical activity (Boles, et al, 2004). Also in this study, consistent with other studies, females were significantly more likely to have any productivity loss than males.…”
Section: Health Symptoms and Health Riskssupporting
confidence: 82%
“…A 20 question health risk assessment tool that contained questions from the Work Productivity and Activity Impairment Questionnaire -General Health (WPAI-GH) tool was used. Consistent with the findings of Burton et al (2006;Burton, et al, 2005), as the number of health risk increased above one, the risk of lost work productivity also increased (Boles, et al, 2004). The total risks for the sample ranged 0 to 9 with a median of 3.…”
Section: Health Symptoms and Health Riskssupporting
confidence: 76%
See 1 more Smart Citation
“…The two last questions are evaluated on a scale of 10 points, ranging from 0 (no effect on work) to 10 (health problems prevent the person from working). 17 The questions are computed according to specifi c calculation rules and have four scores: (1) percentage work time missed due to health (absenteeism); (2) percentage impairment at work due to health (presenteeism); (3) percentage overall work productivity loss due to health (absenteeism and presenteeism); and (4) percentage daily activity impairment outside of work due to health. High scores indicate prolonged sick leave or impairment and decreased productivity.…”
Section: Wpai-gh Productivity Wpai-gh Productivity Assessment Instrummentioning
confidence: 99%